Analysis of Mathematical Problem Solving Ability based on John Dewey’s Theory from The Perspective of Learning Styles - Dewi, Erni Arfiatni; Sari, Rika Mulyati Mustika; Nur, Iyan Rosita Dewi (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Abstract: Problem-solving ability is a primary objective of mathematics learning and can be improved through systematic steps, as proposed by both Polya and John Dewey, particularly in solving contextual problems related to everyday life. Therefore, this study aims to analyze and describe mathematical problem solving abilities in solving contextual problems on matrix material based on John Dewey's theory, and to compare three learning styles: visual, audio, and kinesthetic learning styles. Researchers conducted non-cognitive diagnostic tests to see students' learning styles and mathematical problem solving ability tests, as well as interviews. Data were collected from 32 students (10 visual, 7 audio, and 15 kinesthetic) in class XI Phase F at Sman 1 Sukakarya. This study is a qualitative study using descriptive qualitative research methods. Nine people were selected as research subjects, consisting of three students from each learning style with high, medium, and low ability categories. Data analysis was taken from problem solving ability tests, questionnaires, and interviews. The results showed that the mathematical problem solving abilities of students with a kinesthetic learning style were overall higher than those with visual and audio learning styles. Although students had various learning styles (visual, audio, and kinesthetic), all students demonstrated similar abilities in solving mathematical problems related to matrices. They were all able to articulate arguments, identify facts, perform calculations, compare results, and determine effective strategies. Abstract: Kemampuan pemecahan masalah merupakan tujuan utama pembelajaran matematika dan dapat ditingkatkan melalui langkah-langkah sistematis, baik menurut Polya maupun John Dewey, terutama dalam menyelesaikan soal kontekstual yang dekat dengan kehidupan sehari-hari. Oleh karena itu, penelitian ini bertujuan menganalisis dan mendeskripsikan kemampuan pemecahan masalah matematika dalam menyelesaikan soal kontekstual pada materi matriks berdasarkan teori John Dewey, serta membandingkan tiga gaya belajar, yaitu visual, auditori, dan kinestetik. Peneliti melakukan tes diagnostik nonkognitif untuk mengetahui gaya belajar siswa, tes kemampuan pemecahan masalah matematika, serta wawancara terhadap 32 siswa (10 visual, 7 auditori, dan 15 kinestetik) di kelas XI Fase F SMAN 1 Sukakarya. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif kualitatif. Subjek penelitian berjumlah 9 siswa, yang terdiri atas 3 siswa dari masing-masing gaya belajar dengan kategori kemampuan tinggi, sedang, dan rendah. Analisis data diperoleh dari tes kemampuan pemecahan masalah, angket, dan wawancara. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah matematika siswa dengan gaya belajar kinestetik secara keseluruhan lebih tinggi dibandingkan dengan siswa bergaya belajar visual dan auditori. Meskipun siswa memiliki gaya belajar yang berbeda (visual, auditori, dan kinestetik), seluruh siswa menunjukkan kemampuan yang relatif sama dalam menyelesaikan permasalahan matematika terkait matriks. Mereka mampu mengemukakan argumen, mengidentifikasi fakta, melakukan perhitungan, membandingkan hasil, serta menentukan strategi yang efektif.